1991
DOI: 10.1099/0022-1317-72-4-933
|View full text |Cite
|
Sign up to set email alerts
|

The influence of porcine recombinant interferon- 1 on pseudorabies virus infection of porcine nasal mucosa in vitro

Abstract: To determine the effect of interferon (IFN) on the pathogenesis of pseudorabies virus (PRV), porcine nasal mucosal explants were first treated with recombinant porcine methionyl-IFN-atl and then infected with one of three strains of PRV. The stroma of treated mucosal explants were protected against infection with virulent PRV or PRV of intermediate virulence because the infection was restricted to the epithelial cells. In contrast, untreated mucosal explants were readily infected by virulent PRV or PRV of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Tissue specimens of nasal mucosa, lung, trachea, tonsils, thymus, heart, liver, spleen, kidney, adrenal gland, stomach, duodenum, mesenteric lymph nodes, pancreas, thyroid, and brain were fixed in 10% neutral-buffered formalin and processed as described elsewhere (9).…”
Section: Histological Examinationmentioning
confidence: 99%
“…Tissue specimens of nasal mucosa, lung, trachea, tonsils, thymus, heart, liver, spleen, kidney, adrenal gland, stomach, duodenum, mesenteric lymph nodes, pancreas, thyroid, and brain were fixed in 10% neutral-buffered formalin and processed as described elsewhere (9).…”
Section: Histological Examinationmentioning
confidence: 99%
“…The antiviral activity of PoIFN-α was tested on WISH cells/ Vesicular Stomatitis Virus (VSV) system (LaFleur et al, 2001) and PK 15 cells/Pseudorabies Virus (PRV) system (Pol et al, 1991) respectively. Briefly, the cells were seeded in flat-bottom 96-well plates and grown to 95% confluence, and serial dilutions of PoIFN-α were added to the wells.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…The latter shows the importance of interferon-alpha in the control of virus replication in the nose and pharynx. Using nasal mucosal explants, Pol et al [52] demonstrated that interferon-alpha is diminishing the spread of PrV in the connective tissue but not in the epithelial cells. The reason why epithelial cells are not protected is not understood and should be further analyzed.…”
Section: Virus-respiratory Tract Interactionsmentioning
confidence: 99%